LGSVL Simulator: A High Fidelity Simulator for Autonomous Driving - Rong, Guodong; Shin, Byung Hyun; Tabatabaee, Hadi; Lu, Qiang; Lemke, Steve; Mozeiko, Martins; Boise, Eric; Uhm, Geehoon; Gerow, Mark; Mehta, Shalin; Agafonov, Eugene; Kim, Tae Hyung; et al. (2020 IEEE 23rd International Conference on Intelligent Transportation Systems (ITSC), 2020)
Testing autonomous driving algorithms on real autonomous vehicles is extremely costly and many researchers and developers in the field cannot afford a real car and the corresponding sensors. Although several free and open-source autonomous driving stacks, such as Autoware and Apollo are available, choices of open-source simulators to use with them are limited. In this paper, we introduce the LGSVL Simulator which is a high fidelity simulator for autonomous driving. The simulator engine provides end-to-end, full-stack simulation which is ready to be hooked up to Autoware and Apollo. In addition, simulator tools are provided with the core simulation engine which allow users to easily customize sensors, create new types of controllable objects, replace some modules in the core simulator, and create digital twins of particular environments.